Reflection on Monotheism in QS. Ali-Imran Verses 31, 59, and 128 (Thematic Study Based on Asbābun Nuzūl) - Kholis, Hafidh Dinul; Masruhan, Masruhan; Yudatama, Yossi Kurnia; Huda, Miftahul (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Understanding the historical context of the revelation of the verses of the Qur'an, or what is known as asbābun nuzūl, plays an important role in revealing the theological messages contained therein. Surah Ali 'Imran is one of the surahs that contains profound values of monotheism, spread across several verses that have different backgrounds of revelation. The purpose of this study is to examine the values of monotheism contained in QS Ali 'Imran verses 31, 59, and 128 using the asbābun nuzūl approach, and to explore the dimensions of monotheism in these verses more contextually. This study uses a qualitative method with a descriptive-analytical approach. Analysis was carried out on classical and contemporary sources of interpretation to identify the form of monotheism contained in each verse. The results of the study show that verse 31 contains the teaching of monotheism ulūhiyyah, namely that true love for Allah must be realized through obedience to the Prophet Muhammad. Verse 59 reflects the monotheism of rubūbiyyah, with the assertion that only Allah has full authority as the creator and regulator of the universe. Meanwhile, verse 128 shows the asmāʾ wa ṣifāt dimension of monotheism, with an emphasis on the nature of Allah as the Most Forgiving (al-Ghafūr) and that all decrees belong to Him. Thus, these three verses show that the values of monotheism in Surah Ali 'Imran can be understood more fully and deeply through the asbābun nuzūl approach, which reveals the historical and theological dimensions of revelation.